Electron spin relaxation times and rapid scan EPR imaging of pH‐sensitive amino‐substituted trityl radicals. (12th December 2014) - Elajaili, Hanan B.; Biller, Joshua R.; Tseitlin, Mark; Dhimitruka, Ilirian; Khramtsov, Valery V.; Eaton, Sandra S.; Eaton, Gareth R.
Abstract : Carboxy‐substituted trityl (triarylmethyl) radicals are valuable in vivo probes because of their stability, narrow lines, and sensitivity of their spectroscopic properties to oxygen. Amino‐substituted trityl radicals have the potential to monitor pH in vivo, and the suitability for this application depends on spectral properties. Electron spin relaxation times T 1 and T 2 were measured at X‐band for the protonated and deprotonated forms of two amino‐substituted triarylmethyl radicals. Comparison with relaxation times for carboxy‐substituted triarylmethyl radicals shows that T 1 exhibits little dependence on protonation or the nature of the substituent, which makes it useful for measuring O2 concentration, independent of pH. Insensitivity of T 1 to changes in substituents is consistent with the assignment of the dominant contribution to spin lattice relaxation as a local mode that involves primarily atoms in the carbon and sulfur core. Values of T 2 vary substantially with pH and the nature of the aryl group substituent, reflecting a range of dynamic processes. The narrow spectral widths for the amino‐substituted triarylmethyl radicals facilitate spectral‐spatial rapid scan electron paramagnetic resonance imaging, which was demonstrated with a phantom. The dependence of hyperfine splittings patterns on pH is revealed in spectral slices through the image. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : For amino‐substituted triarylmethyl radicals, T1 is independent of pH, but dynamic processes make T2 pH dependent. The feasibility of rapid‐scan electron paramagnetic resonance imaging of the pH dependence was demonstrated at 250 MHz.